Rancangan Set Alat Peraga Puzzle Dalam Materi Listrik Dinamis - Rasta Br Ginting, Cindy (Universitas Halu Oleo, 2021)
Colicium research has been carried out entitled the design of puzzle props in puzzle material. The purpose of this research is to ascertain the correctness of the puzzle which can be used as a teaching aid in dynamic electrical materials. The tools and materials used are batteries, resistors, incandescent lamps, multimeters, cables, alligator clamps, glue gun, glue, solder, tin and puzzles. The first step in the work procedure of this research is to create an experimental module as a new tool for making puzzles, after which the puzzles are assembled according to the contents of the experimental modules that have been made. And the final stage is to definitely try the tools that have been made to see whether the puzzle that has been made can be used as teaching aids in dynamic electrical materials. The results of this study are that puzzles can be used as teaching aids in dynamic electrical materials, with the proportion of electric tools <5%.